Finding the Inverse of a Function
Given the function f(x) we want to find the inverse function, f−1(x).
- Replace f(x) with y.
- Just rearrange to get x =?
- Then swap the “x”s and “y”s.
- Finally replace y with f−1(x).
Example Given f(x) = 3x−2 find f−1(x).
First y = 3x−2
Next, rearrange to get x. x = y/3 −2/3
Then swap the “x”s and “y”s. y = x/3+2/3
Finally replace y with f−1(x). f−1(x) = x/3+2/3
Example Given f(x) = (5x-2)/(2x+3) find f−1(x).
First y = (5x-2)/(2x+3)
Next, rearrange to get x. y(2x+3) = 5x-2
2yx +3y = 5x-2
2yx -5x = -2-3y
x(2y-5) = -2-3y
x = (-2-3y) / (2y-5)
Then swap the “x”s and “y”s. y = (-2-3x) / (2x-5)
Finally replace y with f−1(x). f−1(x) = (-2-3x) / (2x-5)